Former Yugoslav Republic of Macedonia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues Paper assesses Macedonia's public debt markets and presents recommendations for their further development. Macedonia's domestic debt market is in the early stages of development and is small by regional standards. The paper also analyzes the main causes of euroization in Macedonia. It discusses the nature of monetary policy in Macedonia where despite an exchange rate peg owing to imperfect capital mobility, there exists some degree of autonomy in the conduct of monetary policy in the short term.